Pengaruh Karakteristik Individu Terhadap Motivasi Kerja Karyawan Pt. Solo Murni Di Surabaya - asjari, fachrudy (Fakultas Ekonomi Universitas PGRI Adi Buana, 2013)
Background. This research intended to asses the individual characteristic, to the motivation which must be performed to the employee at PT. Solo Murni in Surabaya. Method. This research was conducted in Surabaya which covered 52 employees as respondent. This research by utilizing Regression, the technique was processed with SPSS 19.0 to analyze some hypothesis. The intercorrelations models between two variables in this study revealed that the hypothesis have significant correlation. Conclusion. The result of this research were empirical date of the development of the theoretical of human resoureces and practice management.